Editorial: Developing lifestyle entrepreneurship for sustainable destinations - Dias, Á.; Simonetti, B.; Bakas, F. E. (Frontiers in Psychology, 2022)
This special issue aims to promote the discussion around lifestyle entrepreneurship which, although being important, as presented in the commentary by Dias and Patuleia, little attention has been paid to the subject. In specific, it is intended to know this specific group of entrepreneurs in more detail in its dimensions of attraction factors, innovation and business development associated with lifestyle.